Cognition and meta-learning through storytelling in educational technology - Peña-Acuña, Beatriz; Herrada-Valverde, Rosario; Herrada-Valverde, Gabriel; Andrychowicz-Trojanowska, Agnieszka (IJERI: International Journal of Educational Research and Innovation, 2025)
The key learning-to-learn competence involves a deeper level of personal learning than simple skills development. With the aim of analysing the development of the competence’s cognitive dimension in the university context, this research presents a digital storytelling intervention undertaken with students from two Spanish universities. Using the Evaluation of Learning to Learn Competence in University Students (CECAPEU) Questionnaire and the data collected from 237 students via a Google Forms questionnaire, a quasi-experimental study with inferential tests was carried out. The results show that most students are distributed between the medium and high competence levels, and that students with good academic performance have better cognitive competence, which is more dependent on subject performance than on their score in the Evaluation Test for University Entrance (PEvAU) or Vocational Training (FP). It is therefore concluded that academic performance in the subject through elaborated interventions is crucial for developing cognitive skills associated with the key learning-to-learn competency.